The geography of medical travel in India: Differences across states, and the urban-rural divide. (June 2019) - Chakrabarti, Sandip; Tatavarthy, Aruna Divya
Abstract: There is a large body of literature exploring spatial disparity in access to healthcare services, and the resultant geographic inequality in the demand for medical travel. We are, however, unaware of any such study conducted in India in the past. The transportation implications of inequitable healthcare access, therefore, remains unknown to Indian planners and policymakers. We use a unique dataset, the 2014–15 Domestic Tourism Expenditure survey conducted by the National Sample Survey Office, Ministry of Statistics and Programme Implementation, Government of India, to address this critical gap in the literature. We use trip-making information of 42, 547 persons (13, 525 urban and 29, 022 rural residents) belonging to 28 Indian states in order to analyze the variation in individuals' medical trip destination choice, on average, across states. We analyze overnight trips (i.e., trips involving at least one night stay away from home) made for medical purposes only. Specifically, we isolate and compare the independent influence of state of residence (i.e., the state-effect) on residents' choice of within-district and out-of-state medical care location, after controlling for various personal and household factors that also govern choice. Additionally, we select a sub-sample of individuals who made out-of-state medical trips, and analyze state-level differences in the likelihood of long or >1500 km (vs. short or ≤1500 km) distance medical travel. We analyze urban and rural residents separately, and estimate a pooled model to explore intra-state urban-rural differences in medical trip destination choice. Our analyses reveal significant variation in urban and rural residents' destination choice for medical trips across India's states. We also find within-state urban-rural differences in destination choice to vary significantly across states. Our analysis provides new information on the geography of medical travel in India, underscoring the need for further research on the causes and consequences of the geographic disparity in healthcare access, and targeted action to improve healthcare access equitably across states. We expect our paper to stimulate further research to guide national and state health and transportation policies in India. Highlights: We use the 2014–15 Domestic Tourism Expenditure survey of India in this study. We analyze variation in urban and rural residents' medical trip destination choice across India's states. We also explore intra-state urban-rural differences in medical travel. Our research provides insights on the geographic inequality of medical travel demand in India. We underscore the need for action to improve healthcare access equitably across states.